Indicators for comparing performance of irrigated agricultural systems - Molden, David J.; Sakthivadivel, Ramaswamy; Perry, C.J.; Fraiture, Charlotte de; Kloezen, W.H. (International Water Management Institute, 1998)
Outlines IWMI's external and other comparative performance indicators that allow for analysis of irrigation performance across systems. The purpose of these indicators is to understand the current situation with respect to productive utilization of land and water, to compare relative performance of systems, and to identify where performance can be improved.